Concentration- and pH-Dependent Oligomerization of the Thrombin-Derived C-Terminal Peptide TCP-25 - Petruk, Ganna (Biomolecules, 2020)
Peptide oligomerization dynamics affects peptide structure, activity, and pharmacodynamic properties. The thrombin C-terminal peptide, TCP-25 (GKYGFYTHVFRLKKWIQKVIDQFGE), is currently in preclinical development for improved wound healing and infection prevention. It exhibits turbidity when formulated at pH 7.4, particularly at concentrations of 0.3 mM or more. We used biochemical and biophysical approaches to explore whether the peptide self-associates and forms oligomers. The peptide showed a dose-dependent increase in turbidity as well as α-helical structure at pH 7.4, a phenomenon not observed at pH 5.0. By analyzing the intrinsic tryptophan fluorescence, we demonstrate that TCP-25 is more stable at high concentrations (0.3 mM) when exposed to high temperatures or a high concentration of denaturant agents, which is compatible with oligomer formation. The denaturation process was reversible above 100 µM of peptide. Dynamic light scattering demonstrated that TCP-25 oligomerization is sensitive to changes in pH, time, and temperature. Computational modeling with an active 18-mer region of TCP-25 showed that the peptide can form pH-dependent higher-order end-to-end oligomers and micelle-like structures, which is in agreement with the experimental data. Thus, TCP-25 exhibits pH- and temperature-dependent dynamic changes involving helical induction and reversible oligomerization, which explains the observed turbidity of the pharmacologically developed formulation.